A quantitative analysis of student competencies in managing dual roles in higher education - Himmi, Nailul; Putri, Retno Sulistiana Anzani; Lestari, Linayati; Surya, Edy; Syahputra, Edi (CAHAYA PENDIDIKAN, 2025)
The increasing phenomenon of student employment affects approximately 30% of Indonesian students, creating complex challenges in balancing academic and professional responsibilities. This quantitative descriptive study examined competency levels among working students managing dual roles in higher education. Using a structured 4-point Likert scale questionnaire, data were collected from 67 working students across UNRIKA, UT, and UNIMED, with supplementary interviews and observations for validation. Descriptive statistical analysis examined eight competency dimensions through frequency distributions and cross-tabulation methods. Results indicated predominance of young females (18-25 years) among working students. High competency levels were demonstrated across multiple areas: 87.5% completed assignments punctually, 76.5% managed stress effectively, and 87.5% exhibited strong communication abilities. Task management and adaptability showed positive outcomes, with 82.9% successfully adjusting academic schedules for work demands and 87.5% prioritizing tasks effectively. However, workload management presented challenges, as 65.7% reported feeling overwhelmed by responsibilities. The statistical findings highlight the need for institutional support mechanisms including flexible learning frameworks, accessible counseling services, and enhanced digital resources. This research contributes empirical evidence for developing targeted interventions to optimize working student competencies, providing measurable insights into dual role management patterns that can inform evidence-based educational policies and support program development in higher education institutions.